2021
DOI: 10.3390/sports9050063
|View full text |Cite
|
Sign up to set email alerts
|

Distance and Intensity Profiles in Division I Women’s Soccer Matches across a Competitive Season

Abstract: Women’s participation in soccer has increased rapidly. The purpose of this study was to evaluate the physiological demands imposed on women’s NCAA Division I soccer players across a season according to speed, total distance traveled, and numbers of sprints measured via GPS (Polar Team Pro®). Eighteen athletes (19.2 ± 1.1 years, 50.5 ± 6.5 mL/kg/min and 23.4 ± 3.6% fat) participated in this study. The analysis was obtained through 13 official matches. Speed zones were defined as Zone 1 (1.0 to 5.99 km·h−1), Zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…Research looking specifically at Division I women's soccer has reported similar relative workloads to those found herein [9,19,21,40], as well as similar positional trends in duration of play [19].…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…Research looking specifically at Division I women's soccer has reported similar relative workloads to those found herein [9,19,21,40], as well as similar positional trends in duration of play [19].…”
Section: Discussionsupporting
confidence: 65%
“…Relative workloads (PL/min, PL/M, M/min), which are more commonly reported in the literature, fail to demonstrate the duration of the load experienced, which can ultimately demonstrate varying degrees of vulnerability for fatigue. Workloads were assessed by game half to further support how factors such as fatigue or reduced demands may contribute to trends; similar to previous research, both external and internal workloads herein were consistently lower in the second half [9,31,32,43,44].…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations